Acute Invasive Fungal Rhinosinusitis-Related Orbital Infection: A Single Medical Center Experience. (12th June 2021) - Huang, Yu-Fang; Liang, Kai-Li; Liang, Chiao-Ying; Yang, Po-Chin; Chen, Jun-Peng; Wei, Li-Chen
Abstract : Backgrounds . Acute invasive fungal rhinosinusitis (AIFRS) is a hazardous infectious disease with rapid progression and high mortality and morbidities. Further orbital involvement is commonly seen. This study aims to analyze risk factors, clinical characteristics, and outcomes between patients with or without orbital involvement. Methods . A retrospective review was performed in a single tertiary medical center over a span of 13 years (2005–2018). A total of 21 patients with diagnosis of AIFRS were enrolled. We reviewed the patients' basic characteristics, comorbidities, clinical presentations, image study findings, culture pathogens, and treatment outcomes and analyzed the differences between orbital-involved and orbital sparing disease. Results . The most common comorbidities in AIFRS were diabetes mellitus (DM) and hematological malignancy. Nine the 21 AIFRS patients had orbital-involved disease. Patients with orbital involvement had a higher prevalence of DM (p < 0.05 ). Image studies revealed significant infection of the ethmoid sinus, sphenoid sinus, and frontal sinus in the group with orbital complication (p < 0.05 ). Mucor, Rhizopus, and Aspergillus were cultured in both groups. Five patients in the orbital involvement group expired, with all of them having an initial presentation of conscious disturbance (p < 0.01 ). Rhino-orbital-cerebral fungal infection was noticed in 3 of the 5 expired patients. Conclusion . In AIFRS patients, DM other than hematological malignancy was the main risk factor for orbital-involved disease. Patients with ethmoid, sphenoid, or frontal sinusitis had a higher possibility of orbital complication. Poor consciousness at initial presentation revealed highest possibility of rhino-orbital-cerebral fungal infection and led to death.